INOVASI UNTUK MENINGKATKAN LITERASI DIGITAL PADA MAHASISWA KEPERAWATAN - Sondang Ratnauli Sianturi; Hany Wihardja (Jurnal Surya Muda, 2021)
Digital literacy in nursing students is necessary in this case where the rapid technology development. Knowledge and skills of digital literacy can be improved by the lecture integrated and combined with increasing skill. Increasing digital literacy aims to enable students to access, understand information technology and make digital innovations that are useful for nursing. This innovative design provides an overview of the innovations made by nursing students and which services can be utilized. The innovative design is carried out in several stages: first, students analyze the situation in the nursing environment so that students make innovation that can help nurses work: second, determine the innovation design; third, making innovations and being presented. The method used is quantitative by distributing questionnaires to participants who tried the innovation designs on display and students were divided into 10 groups with 10 innovation designs. This innovative design was carried out for two weeks. The results of this activity was 90% of the designs made have applicative value and useful for nurses. The application of digital literacy in designing this innovation becomes a medium for improving nursing student technology. This activity is expected to be input and support nursing students and increase digital literacy in Indonesia.